Psychometric Properties of a Turkish Version of the Assessment of Physiotherapy Practice Tool - Yakut, Y; Polat, MG; Sisli, H; Avci, EE; Demirbuken, I; Cakir, F (Physıotherapy Research Internatıonal)
Background and Purpose: Assessment of physiotherapy undergraduate students in clinical placement is academicallyimportant and holds practical value. This study aimed to translate the Assessment of Physiotherapy Practice (APP) tool, whichis widely used for this purpose, into Turkish and to verify the factor validity and examine the reliability of this version using across‐sectional design on senior physiotherapy students.Methods: The APP and performance indicators were translated into Turkish in accordance with the recommended protocol.Exploratory and confirmatory factor analyses were conducted using scale data from 100 students. For reliability analyses, 10clinical supervisors from a Turkish university assessed 63 students using the Turkish version of the Assessment of Physio-therapy Practice (APP‐TR) tool. Supervisors performed the APP‐TR assessment for each student at week 3 and at the end of the6‐week clinical placement, yielding a score for analysis.Results: In both assessments, the scale demonstrated high levels of internal consistency (Cronbach's α = 0.961 for the firstassessment, 0.959 for final assessment). Two factors were identified by exploratory factor analysis explaining 65.84% of the totalvariance and a two‐factor model was confirmed to fit by confirmatory factor analysis. Test‐retest reliability was assessed by ICCand was high for all subheadings and total score. For all items, the close agreement was at least 98.41% and the exact agreementwas at least 88.89% in the percentile analysis between the two assessments.Discussion: The results of this study suggest that the APP‐TR is a reliable and valid tool for evaluating final year physiotherapystudents in a clinical placement in Turkey.
Keywords: educational measurement; internal consistency; intra‐rater reliability